Proses Sintesis dan Karakterisasi Hydoxyapatite Menggunakan Analisis XRD FTIR dari Gypsum Puger Kabupaten Jember sebagai Material Augmentasi Ridge Alveolar - Amiyatun Naini; Hengky B. Ardhiyanto; Yenny Yustisia (Fakultas Kedokteran Gigi Universitas Jember, 2014)
Tooth extraction can cause alveolar ridge resorption that affect the use of the denture, so it requires augmentation to improve the contour of the alveolar ridge. Hydroxyapatite is used as alveolar ridge augmentation material in Indonesia, they are imported at high prices and availability limited. In Indonesia, especially the area of ​​East Java Jember district Puger produced natural gypsum raw materials that can be developed and utilized as hydroxyapatite. This study aims to determine how the process of synthesis and characterization Hydoxyapatit using FTIR XRD analysis of Gypsum Puger Jember as alveolar ridge augmentation material. Methods of synthesis of hydroxyapatite research conducted by hydrothermal technique by reaction between gypsum hydroxyapatite Puger with DHP (diammonium hydrogen phosphate), then the result of the reaction was analyzed by XRD and FTIR testing compared with HA 200 Japan as a comparison. The results of the analysis we found the same patterns between Gypsum hydroxyapatite Puger with HA 200 Japan as standard. Conclusion The study has managed to synthesize gypsum puger into hydroxyapatite / Puger gypsum hydroxyapatite (HAGP). Characterization HAGP performed by XRD and FTIR that test results are the same, or there is a similar pattern with HA 200 Japan (standard), so HAGP is one of the bioceramics materials that can be used as an alternative material alveolar ridge augmentation in order to use denture can be managed properly.